Integrasi Sentrifugasi Suhu Rendah dengan Optimasi Ekstraksi Enzimatis Minyak Mata Tuna menggunakan Response Surface Methodology: Integration of Low Temperature Centrifugation with Optimization of Tuna Eye Oil Enzymatic Extraction Using Response Surface Methodology - Wini Trilaksani; Bambang Riyanto; Tati Nurhayati; Joko Santoso; Ikram Abi Hamzah Kurniawan (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Tuna eye oil which is rich in omega-3 fatty acids eicosapentaenoic acid and docosahexaenoic acid can be obtained by low temperature extraction however the yield was not optimum yet. The yield value of tuna eye oil can be increased with enzymatic hydrolysis. Response Surface Methodology (RSM) can help analyze the effect of factors on the response to optimize the conditions of enzymatic hydrolysis. The purpose of this study was to maximization of oil yield, determine the optimum conditions for enzymatic extraction of tuna eye oil with different papain enzyme concentration and hydrolysis time using central composite design-face centered (CCDFC) modeling on RSM and determination of oil characteristics. The validation optimum of the enzymatic hydrolysis resulted in a yield value of 11.24±0.09% at the concentration of 1.02% papain enzyme for 3 hours. The EPA and DHA content of tuna eye oil at the optimum condition was classified as very high, 6.02% EPA and 30.30% DHA from 99.90% of the total identified fatty acids.